WHAT TOURISM PRODUCT ATTRIBUTES ARE DOMINANT INFLUENCING REVISIT INTENSION TO CULINARY TOURISM DESTINATION? - Ingkadijaya, Rahmat; Bilqis, Linda Desafitri Ratu; Nurlaila, R. Nirmalasari (Jurnal Ilmu Sosial dan Humaniora, 2021)
Culinary tourism is a form of tourism that is currently developing. Studies on the preferences of culinary tourists will be beneficial for the development of this form of tourism in the future. This study analyzes the influence of tourism product attributes: tourist attraction, accessibility, and amenities on revisit intention to a culinary tourism area. This study used a survey method. The questionnaire was distributed to 100 domestic tourists who visited the culinary tourism area in Bogor City, Indonesia. Methods of data analysis using descriptive analysis, multiple regression, F-test, and T-test. This study indicated that tourist attraction has a positive and significant effect on revisit intention, while accessibility and amenities do not affect revisit intention. However, tourist attraction, accessibility, and amenities simultaneously have a positive and significant effect on revisit intention. This study concluded that the dominant attribute of culinary tourism products is a tourist attraction that includes a variety of food and distinctiveness.